2013
DOI: 10.1177/019874291303900106
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Integrating Social-Emotional Learning with Literacy Instruction: An Intervention for Children at Risk for Emotional and Behavioral Disorders

Abstract: It is widely believed that children's social-emotional growth and academic learning are inextricably connected. Pressured by high-stakes assessments, however, school professionals find it difficult to devote adequate time to children's social/behavioral development. As a response, we developed and piloted Social-Emotional Learning Foundations (SELF), a curriculum for students at risk for emotional or behavioral problems that merges instruction in social-emotional learning with early literacy skills. Designed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Developing children's EL facilitates changing established patterns of behaviour (Daunic et al ., ; Corrie, ). This may be conceptualised as a means of empowering children to understand and manage emotions to enable them to handle social situations (Camerelli et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing children's EL facilitates changing established patterns of behaviour (Daunic et al ., ; Corrie, ). This may be conceptualised as a means of empowering children to understand and manage emotions to enable them to handle social situations (Camerelli et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…These role models were successful at explaining their ideas clearly without dominating the group. Activities, such as role‐play, predicated upon experiential learning approaches, may also support comprehension and developing new competences (Daunic et al ., ; Camerelli et al ., ). Overall, the data suggests that although some pro‐social behaviour had improved, the children's ability to resolve disputes had not.…”
Section: Discussion: Key Findings and Critiquementioning
confidence: 97%
“…In aligment with other previous studies, strong and positive correlations between different components of SEL were also found in this study. Previous studies have found that there is a positive correlation between self-awareness and health and emotion (Daunic et al, 2013), expectancy (Durlak et al, 2011, life satisfaction (Jones et al, 2015), anti-social behaviors, and school absenteeism (Brackett et al, 2004). It is suggested that teaching methods for the development of self-awareness from the other countries could be learnt to be applied into the Vietnamese education program.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies showed the positive correlation between relationship skills and emotional health (Hattie, 2009), negative correlation with anti-social behaviors (Garner, 2010) and mental health such as anxiety and depression (Daunic et al, 2013). In general, there is a spread of relationship skills competence among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increased focus on the necessity to integrate social-emotional learning (SEL) with academic instruction for students, especially those at risk for emotional and behavioral problems in the United States (Berger et al, 2011; Daunic et al, 2013; Elias and Haynes, 2008; Liu et al, 2017). Researchers have found that SEL is crucial for mental health and overall wellbeing (Denham, 2006; Heller et al, 2012), and is one of the most important abilities supporting school success later in life (Morgan et al, 2008).…”
mentioning
confidence: 99%